An assessment of the environmental impact of large scale deer farming in Sarawak - Wong, Thomas Kee Ung (Universiti Malaysia Sarawak (UNIMAS), 2005)
Deer farming is one way of conservation and sustainable use of our natural resources. There are a number of large-scale deer farms with Sam bar and rusa deer belonging to both the government and private sectors in Sarawak. There is, however, a dearth of information on current practices in deer farming and their impacts on the environment. The study examined the interaction and impact of deer production on soil fertility, forage nutritive values, water quality and soil loss in two large scale farms rearing a total of 728 heads of rusa. Fawning performance and stocking rates were also assessed. The findings indicated that soil nutrient levels, forage nutritive values and deer performance appear acceptable under current practices. Water quality is of some concern with increased coliforms and Escherichia coli counts from the land use. Critical pasture management and soil conservation practices need to be adopted to mitigate the effect and impact of deer farming on environmental quality.